Halorubrum marinum sp. nov., Halorubrum rarum sp. nov., Halorubrum wangae sp. nov., Halorubrum shenae sp. nov., and Halorubrum zhoui sp. nov., halophilic archaea from coastal tidal flats, a saline lake, and a marine solar saltern - Qing-Di Li; Yang-Yang Wang; Chidiebele Nwankwo; Yao Hu; Xin-Yue Dong; Jing Hou; Xiang-Dong Chen; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Space-confined composition-gradient perovskite for computational microspectrometer - Zhenhua Zhang; Hanyu Cui; Chenyan Zhuang; Xiaoxuan Wang; Heng Guo; Baohao Lin; Wanyu Wang; Wendong Lu; Zengliang Shi; Chunxiang Xu (Chemical Engineering Journal, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Natronorubrum marinum sp. nov., Natronorubrum amylolyticum sp. nov., Natronorubrum halobium sp. nov., and Natronorubrum salinum sp. nov., halophilic archaea from a coastal saline-alkali land and two saline lakes - Ya-Ling Mao; Yao Hu; Zhang-Ping Wu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Halosimplex amylolyticum sp. nov., Halosimplex halobium sp. nov., Halosimplex marinum sp. nov., Halosimplex rarum sp. nov., Halovenus amylolytica sp. nov., Halovenus halobia sp. nov., and Halovenus marina sp. nov., halophilic archaea isolated from a marine tidal flat, a marine solar saltern, three coarse sea salts, and two saline lakes - Ya-Ling Mao; Shun Tan; Bei-Bei Wang; Xiao-Yan Yang; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Halobellus marinus sp. nov., Halobellus ordinarius sp. nov., Halobaculum rarum sp. nov., and Halorarum halobium sp. nov., halophilic archaea isolated from marine solar salt and a saline lake - Ling-Rui Zhu; Chidiebele Nwankwo; Jing Hou; Heng-Lin Cui (Extremophiles, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Natronorarus salvus gen. nov., sp. nov., Halalkalicoccus ordinarius sp. nov., and Halalkalicoccus salilacus sp. nov., halophilic archaea from a soda lake and two saline lakes, and proposal to classify the genera Halalkalicoccus and Natronorarus into Halalkalicoccaceae fam. nov. in the order Halobacteriales within the class Halobacteria - Ya-Ling Mao; Xin-Yue Dong; Cong-Qi Tao; Zhang-Ping Wu; Xiao-Wei Shi; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Genome-Based Classification of ‘Haloarcula aidinensis’ and Description of Three Novel Halophilic Archaea Isolated from an Inland Saline Lake, Coastal Saline Soil, and a Marine Solar Saltern - Xue Ma; Yao Hu; Jing Hou; Yu-Guang Zhou; Heng-Lin Cui (Current Microbiology, 2024)

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

A hyperstable, low-salt adapted protease from halophilic archaeon with potential applications in salt-fermented foods - Jing Hou; Qing-Ke Zhang; Ruo-Yao Zhang; Si-Ya Li; Yuan-Yiyi Liu; Heng-Lin Cui (Food Research International, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Halomontanus rarus gen. nov., sp. nov., a novel halophilic archaeon of the family Natrialbaceae from salt lakes on the Qinghai-Xizang Plateau - Ya-Ling Mao; Bei-Bei Wang; Xue-Meng Yin; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Halorubrum hochsteinianum sp. nov., an ancient haloarchaeon from a natural experiment - Russell H. Vreeland; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

An extracellular protease containing a novel C-terminal extension produced by a marine-originated haloarchaeon - Dong Han; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Marine microorganisms have long been acknowledged as a significant reservoir of enzymes required for industrial use. In this study, a novel extracellular protease Hsl HlyB derived from marine-originated haloarchaeon Halostella pelagica DL-M4 T was identified. Hsl HlyB contained polycystic kidney disease (PKD) domain and pre-peptidase C-terminal (PPC) domain at the C-terminus. Truncation and replacement of the C-terminal extension (CTE) of Hsl HlyB demonstrated the importance of the CTE in maintaining the protease activity secreted by haloarchaeon. Hsl HlyB and Hsl HlyBΔCTE were expressed in Escherichia coli BL21(DE3), and purified by high-affinity column refolding and gel filtration chromatography. The molecular masses of Hsl HlyB and Hsl HlyBΔCTE were 42 kDa and 20 kDa, respectively. The optimum catalytic reaction conditions were 50°C, pH 8.5, NaCl 3.5 M and 50°C, pH 7.5, NaCl 3 M, respectively. They showed good stability and hydrolysis capabilities towards a wide range of protein substrates. Hsl HlyBΔCTE showed higher catalytic reaction rate and better thermal stability than the wild type against azocasein and tetrapeptide substrate. The hydrolysates of soybean protein hydrolyzed by Hsl HlyBΔCTE had smaller average molecular masses and shorter average peptide chain lengths than those by Hsl HlyB. These results indicated the diversity of halolysins from marine-originated haloarchaea to harness organic nitrogen in the marine environment and provided promising candidates for application in various industries.

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Halocatena marina sp. nov., a novel filamentous halophilic archaeon isolated from marine tidal flat and emended description of the genus Halocatena - Zhang-Ping Wu; Xi-Wen Zheng; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Halorarius litoreus gen. nov., sp. nov., Halorarius halobius sp. nov., Haloglomus halophilum sp. nov., Haloglomus salinum sp. nov., and Natronomonas marina sp. nov., extremely halophilic archaea isolated from tidal flat and marine solar salt - Ya-Ping Sun; Bei-Bei Wang; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Five novel halophilic archaeal strains, named BND22 T , ZY10 T , ZY41 T , ZY58 T , and ZY43 T , were isolated from the coastal saline sediment of the intertidal zone located in Qingdao and the natural sea salt produced from Huanghua marine solar saltern, PRChina. These five strains demonstrated the typical morphology and growth characteristics of haloarchaea. The comparison of 16S rRNA gene revealed that strain BDN22 T was associated with Salinirubellus salinus ZS-35-S2 T (95.2% similarity), strain ZY10 T was related to Halosegnis rubeus F17-44 T (95.1% similarity), both strains ZY41 T and ZY58 T were closely related to Haloglomus irregulare F16-60 T (98.1% and 98.2% similarities, respectively), and strain ZY43 T was close to Natronomonas salina YPL13 T (98.0% similarity). In addition to the 16S rRNA gene, the rpoB′ gene is undoubtedly another important molecular marker for the identification of halophilic archaea, and concatenated-conserved-protein phylogeny was widely used in archaeal classification in recent years. Phylogenetic and phylogenomic analyses based on rpoB′ genes and 122 concatenated archaeal protein genes showed that these haloarchaea construct three different clades and gathered together with the current members of Haloarculaceae . Strains BND22 T and ZY10 T formed two distinct clades separated from Salinirubellus salinus ZS-35-S2 T and Halosegnis members, strains ZY41 T and ZY58 T clustered with Haloglomus irregulare F16-60 T , and strain ZY43 T gathered with the current members of Natronomonas. The ANI, DDH, and AAI values of these five strains against phylogenetic neighbours were no more than 91%, 45%, and 92%, respectively, far below the cut-off values for species delineation, supporting their placements in new taxa. Based on the phenotypic, chemotaxonomic, phylogenetic, and phylogenomic properties, these five strains represent five novel taxa of the family Haloarculaceae , Halorarius litoreus gen. nov., sp. nov. (type strain BND22 T = CGMCC 1.18780 T = JCM 34966 T ), Halorarius halobius sp. nov. (type strain ZY10 T = CGMCC 1.17475 T = JCM 34319 T ), Haloglomus halophilum sp. nov. (type strain ZY41 T = CGMCC 1.17030 T = JCM 34161 T ), Haloglomus salinum sp. nov. (type strain ZY58 T = CGMCC 1.17216 T = JCM 34163 T ), and Natronomonas marina sp. nov. (type strain ZY43 T = CGMCC 1.17202 T = JCM 34162 T ). This is the first report of description of a novel haloarchaeon isolated from a marine intertidal zone.

Halorussus vallis sp. nov., Halorussus aquaticus sp. nov., Halorussus gelatinilyticus sp. nov., Halorussus limi sp. nov., Halorussus salilacus sp. nov., Halorussus salinisoli sp. nov.: six extremely halophilic archaea isolated from solar saltern, salt lake and saline soil - Xi-Wen Zheng; Zhang-Ping Wu; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Halorientalis salina sp. nov., Halorientalis marina sp. nov., Halorientalis litorea sp. nov.: three extremely halophilic archaea isolated from a salt lake and coarse sea salt - Bei-Bei Wang; Ya-Ping Sun; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Haloprofundus salilacus sp. nov., Haloprofundus halobius sp. nov. and Haloprofundus salinisoli sp. nov.: three extremely halophilic archaea isolated from salt lake and saline soil - Si-Ya Li; Yu-Jie Xin; Chen-Xi Bao; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Cultivation of halophilic archaea (class Halobacteria) from thalassohaline and athalassohaline environments - Heng-Lin Cui; Mike L. Dyall-Smith (Marine Life Science & Technology, 2021)

Halorussus halophilus sp. nov., A Novel Halophilic Archaeon Isolated from a Marine Solar Saltern - Yi Ding; Dong Han; Heng-Lin Cui (Current Microbiology, 2020)

Characterization of a novel Cu-containing dissimilatory nitrite reductase from the haloarchaeon Halorussus sp. YCN54 - Jing Hou; Xiao-Yan Yang; Qin Xu; Heng-Lin Cui (Extremophiles, 2020)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Haloprofundus halophilus sp. nov., isolated from the saline soil of Tarim Basin - Qin Xu; Heng-Lin Cui; Fanwei Meng (Antonie van Leeuwenhoek, 2019)

In Vitro Antioxidant, Antihemolytic, and Anticancer Activity of the Carotenoids from Halophilic Archaea - Jing Hou; Heng-Lin Cui (Current Microbiology, 2018)

Halobium Salinum sp. nov., Isolated from a Marine Solar Saltern - Yang Li; Yao Zhou; Zhen-Zhen Lü; Heng-Lin Cui (Current Microbiology, 2018)

Halomarina rubra sp. nov., isolated from a marine solar saltern - Yao Zhou; Yang Li; Zhen-Zhen Lü; Heng-Lin Cui (Archives of Microbiology, 2017)

Halorussus salinus sp. nov., isolated from a marine solar saltern - Jia-Qi Xu; Wen-Mei Xu; Yang Li; Yao Zhou; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Archives of Microbiology, 2016)

Halomarina salina sp. nov., isolated from a marine solar saltern - Wen-Mei Xu; Jia-Qi Xu; Yao Zhou; Yang Li; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Antonie van Leeuwenhoek, 2016)

Halorubrum rutilum sp. nov. isolated from a marine solar saltern - Shuai Yin; Zhao Wang; Jia-Qi Xu; Wen-Mei Xu; Pan-Pan Yuan; Heng-Lin Cui (Archives of Microbiology, 2015)

Halorientalis brevis sp. nov., Isolated from an Inland Salt Lake of China - Pan-Pan Yuan; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Current Microbiology, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Halosimplex litoreum sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Jia-Qi Xu; Wen-Mei Xu; Zhao Wang; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Halorussus ruber sp. nov., isolated from an inland salt lake of China - Wei-Dong Xu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Kun Yang (Archives of Microbiology, 2015)

Halorubrum laminariae sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Halobacterium rubrum sp. nov., isolated from a marine solar saltern - Dong Han; Heng-Lin Cui (Archives of Microbiology, 2014)

Halopenitus salinus sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2014)

Halorubrum salinum sp. nov., isolated from a marine solar saltern - Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2014)

Haloarchaeobius litoreus sp. nov., isolated from a marine solar saltern - Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2014)

Haloplanus litoreus sp. nov. and Haloplanus ruber sp. nov., from a marine solar saltern and an aquaculture farm, respectively - Dong Han; Heng-Lin Cui (Antonie van Leeuwenhoek, 2014)

Erratum to: Salinarubrum litoreum gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from Chinese marine solar salterns - Heng-Lin Cui; Xing-Xing Qiu (Antonie van Leeuwenhoek, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Salinarubrum litoreum gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from Chinese marine solar salterns - Heng-Lin Cui; Xing-Xing Qiu (Antonie van Leeuwenhoek, 2014)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Halohasta litorea gen. nov. sp. nov., and Halohasta litchfieldiae sp. nov., isolated from the Daliang aquaculture farm, China and from Deep Lake, Antarctica, respectively - Yun-Zhuang Mou; Xing-Xing Qiu; Mei-Lin Zhao; Heng-Lin Cui; Dickson Oh; Mike L. Dyall-Smith (Extremophiles, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Evaluating the prevalence and molecular epidemiology of echovirus 11 isolated from sewage in Shandong Province, China in 2010 - Jing Yang; Ning Cui; Haiyan Wang; Zexin Tao; Yao Liu; Heng Zhang; Hiromu Yoshida; Yanyan Song; Yong Zhang; Lizhi Song; Yan Li; Xiaojuan Lin; et al. (Virus Genes, 2012)

Salinarchaeum laminariae gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from salted brown alga Laminaria - Heng-Lin Cui; Xin Yang; Yun-Zhuang Mou (Extremophiles, 2011)

Halorussus rarus gen. nov., sp. nov., a new member of the family Halobacteriaceae isolated from a marine solar saltern - Heng-Lin Cui; Xia Gao; Xin Yang; Xue-Wei Xu (Extremophiles, 2010)

Intraspecific polymorphism of 16S rRNA genes in two halophilic archaeal genera, Haloarcula and Halomicrobium - Heng-Lin Cui; Pei-Jin Zhou; Aharon Oren; Shuang-Jiang Liu (Extremophiles, 2009)